What do we know about the future of measuring food systems? - Fanzo, Jessica; Carducci, Bianca; Puma, Michael J. (CGIAR, 2024)
Key messages -Many food system-related databases, tools, and dashboards are available, but to ensure these tools are helpful for decision-makers, they must be harmonized and their sophistication increased to capture trade-offs and synergies. -The Food Systems Countdown Initiative holds great potential to address this need, but its success will depend on several factors, such as filling national and subnational data gaps, ensuring countries formalize their commitments, translating global ambitions into national contexts, and integrating sectoral policies and programs. -A new generation of food system indicators must capture multifaceted interactions, trade-offs, and synergies by integrating observations, models, and complex system analyses with clear metadata for appropriate use.